Two kinds of Pyrus Ussurian pears pomace analysis of physicochemical properties and their effects on the production of ham sausage - YANG Xiaokuan; CHANG Xuedong (浙江大学学报. 农业与生命科学版)
Today, “healthy foods” are a popular trend, and consumers are fonder of low-calorie, high-fibre foods. Dietary fibre refers to the parts of fruits, vegetables, crops, nuts and legumes that cannot be digested by humans. Dietary fibre has lower serum cholesterol, improves intestinal function and reduces the residence time of food residues in the intestine. It is a well-established fact that the consumption of adequate amounts of dietary fibre can prevent high blood pressure, high blood fat, arteriosclerosis, coronary heart disease, diabetes, constipation and other diseases. In the past 50 years, the development of dietary fiber and its application in food have become a hot research topic in the world long range. Pyrus Ussurian pears, commonly known as sour pear, is one of the representative varieties of Pyrus Ussuriensis Maxim system, mainly distributed in northeast Hebei, Beijing and Tianjin and other places in the west and the Yanshan area, with the annual output of 100 thousand tons, which is one of the oldest cultivated varieties. The processing of the pears is mainly made of pear juice beverage and wine brewing pear, and its processing P. Ussurian pears pomace (PUPP) by-products rich in dietary fiber has often been abandoned, which not only pollute the environment but also waste dietary fiber resources. Thus, the addition of PUPP as a functional ingredient into meat products after processing, can not only solve the problem of pollution, but also achieve the reuse of dietary fiber resources.In order to improve the utilization rate of P. Ussurian pear resources, PUPP as a source of dietary fiber was used in ham sausage, and improve the nutrition structure of ham sausage to explore the feasibility of developing high fiber ham sausage. This paper studied basic components and physicochemical properties of peeled P. Ussurian pears pomace (PPUPP) and whole-fruit P. Ussurian pears pomace (WFPUPP) as well as PUPP as a source of dietary fiber added to ham sausage.The results showed that the moisture, ash content, fat content, water-holding capacity, oil-holding capacity, water solubility index and chroma L* & b* value of the two kinds of PUPP were significantly different, the differences in protein, starch, dietary fiber content, pH value, chroma a* value were not significant. The effect of ham sausage physicochemical properties of the two kinds of PUPP in different levels is not significant, and PUPP has significant effect on the textural properties. The hardness and chewiness increased with PUPP level. The hardness of the treatments added with WFPUPP and PPUPP ham sausage was increased from 3.16 N of the control group to 4.74 N and 5.00 N, respectively. While the chewiness was increased from 21.70 mJ of the control group to 32.45 mJ and 28.73 mJ, respectively. Ham sausage glue viscosity and elasticity decreased with the level of PUPP, which the viscosity in the treatment of WFPUPP and PPUPP ham sausage was reduced from 8.33 mJ in the control group to 3.67 mJ and 6.04 mJ and from 14.67 N elasticity in the contrast group to 12.05 N and 12.81 N, respectively. Different addition levels of PUPP showed significant influence on ham sensory properties including color, texture and taste, but there was no significant difference in flavor. The overall acceptability of ham added with 0.5% PUPP was the closest to the control group.0.5% 2.0% PUPP showed no significant effect on the overall acceptability of ham, and the highest level of two kinds of PUPP incorporated into ham was 2.0%.